Environmental Rights and Article 2 of the ECHR: A Focus on Central and Eastern European Jurisprudence - Bitadze, Maia (Human Rights and Environmental Protection from a Central and Eastern European Perspective, 2026)
Living in the 21st century means living in an era filled with new opportunities and novel challenges. This era has brought humanity economic development, industrial growth, and technological progress, resulting in overall improved well-being. However, this same progress is closely linked to harmful impacts on the human environment, such as daily exposure to harmful anthropogenic influences, soil and air pollution, water contamination and scarcity, resource depletion, deforestation, loss of biodiversity, and other natural and human-made risks exacerbated by climate change and industrial expansion. People are particularly vulnerable in urban and industrial zones, where the living environment becomes unnatural and unsuitable for humans as biological beings. While the right to life as a fundamental principle in human rights law was traditionally understood as protection against arbitrary deprivation of life, in the contemporary context, this right has evolved and encompasses not only the protection of existence in a physical sense but also the quality under which life is lived. Therefore, it is crucial that each state, at both the national and international levels, creates legislative and enforcement systems that allow individuals to benefit from the economic advancements of the 21st century while also being protected from the various factors contributing to environmental pollution and degradation. As such, environmental protection must be viewed as a critical aspect of ensuring the right to life, necessitating proactive and sustained efforts at all levels of governance. The effective administration of justice is of paramount importance in this context, particularly regarding the jurisprudence of the European Court of Human Rights (ECtHR). Through the application of the “par ricochet” principle, the ECtHR has firmly established that a contaminated environment adversely affects human health, poses a significant risk to life, and consequently constitutes a violation of Article 2 of the European Convention on Human Rights – the right to life.